Uma proposta de jogo matemático na Educação de Jovens e Adultos (EJA): reforçando conceitos de porcentagem - Ribeiro, Sandra Martins Carlos (2021)
This College Project presents the trajectory the Youth and Adult Education trajectory (EJA) in Brazil and Minas Gerais. Narrating every study from the time of the Jesuits, with the arrival of the Royal Family in Brazil, until nowadays. In addition to bringing the specifics of the public that attends it, noteworthy, EJA students have a different profile, as most of them were out of school for many reasons, as economic and social. Most students of this modality are people who work during the day and study at night, arriving tired at school. Therefore, it is important for the teacher to use different teaching methodologies, so that the teaching and learning relationship does not become routine and exhausting, especially in Mathematics. Through a search for scientific works, articles, dissertations and theses by several authors, a bibliographical research was developed, aiming to verify the importance of games to facilitate the teaching and learning of mathematics, mainly in EJA. Thus, we bring the proposal to use a board game, called ’The Financial Trail’, in order to make learning fun, shearching for minimize the difficulties present in the contents worked with Percentages, taking advantage of the existing social interaction, considering the experience of EJA student’s life and aiming to collaborate with students’ daily problems solving.